New Technologies to Prevent Anastomotic Leak - Uppal, Abhineet; Pigazzi, Alessio (Clinics in Colon and Rectal Surgery, 2021)
Leaks from anastomoses can be a serious complication of any gastrointestinal resection. Leaks lead to increased morbidity, delayed postoperative recovery, and potential delays in adjuvant treatment in cancer cases. Prevention of anastomotic leak has been an area of ongoing research for decades. Methods of assessing bowel perfusion have been developed that may provide forewarning of anastomotic compromise. Physical reinforcement of the anastomosis with buttressing material is an available method employed with the goal of preventing leaks. Liquid-based sealants have also been explored. Lastly, interactions between the gut microbiome and anastomotic healing have been investigated as a mean of manipulating the microenvironment to reduce leak rates. Though no single technology has been successful in eliminating leaks, an understanding of these developing fields will be important for all surgeons who operate on the gastrointestinal tract.
Keywords: anastomosis; colorectal surgery; anastomotic leak; bowel perfusion; endoscopy